2018
DOI: 10.31395/2310-0478-2018-21-21-24
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Photosynthetic Productivity of Soybean Crops for the Use of Different Types of Fungicides and Inoculants in the Right-Bank Forest-Steppe of Ukraine

Abstract: Мостов'як І. І., кандидат с.-г. наук, доцент Уманський національний університет садівництва аспірант Уманський національний університет садівництва Кравченко О. В. 'Я \ ФОРМУВАННЯ ФОТОСИНТЕТИЧНОЇ ПРОДУКТИВНОСТІ ПОСІВІВ СОЇ ЗА ВИКОРИСТАННЯ РІЗНИХ ВИДІВ ФУНГІЦИДІВ ТА ІНОКУЛЯНТА У ПРАВОБЕРЕЖНОМУ ЛІСОСТЕПУ УКРАЇНИ Анотація. У статті наведено результати досліджень з вивчення фотосинтетичної діяльності посівів сої за використання різних видів фунгіцидів та інокулянта Ризоактив. Об'єктами досліджень слугували рослини… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This can be explained by the decrease in the toxic effect of the applied to the seeds fungicide as the plant biomass increases, as well as by the activation of protective systems against the action of xenobiotics, and the positive role of fungicides in the protection against fungal phytopathogens. The latter, in particular, is indirectly confirmed by a significant increase of the chlorophyll index at the flowering stage of plants, whose seeds were treated with fungicides, compared with control (Tab 2), as well as by the literature data concerning the use of fungicides on soybean under field conditions (Mostoviak et al, 2018). These results are consistent with our previous studies, which found that fungicides inhibit the formation and functioning of soybean symbiotic systems at the early stages of plant development, and can shift the peak of nitrogen-fixing activity to later stages of ontogenesis (Pavlyshche et al, 2017).…”
Section: Photosynthetic Apparatus Capacity and Plant Productivitymentioning
confidence: 60%
“…This can be explained by the decrease in the toxic effect of the applied to the seeds fungicide as the plant biomass increases, as well as by the activation of protective systems against the action of xenobiotics, and the positive role of fungicides in the protection against fungal phytopathogens. The latter, in particular, is indirectly confirmed by a significant increase of the chlorophyll index at the flowering stage of plants, whose seeds were treated with fungicides, compared with control (Tab 2), as well as by the literature data concerning the use of fungicides on soybean under field conditions (Mostoviak et al, 2018). These results are consistent with our previous studies, which found that fungicides inhibit the formation and functioning of soybean symbiotic systems at the early stages of plant development, and can shift the peak of nitrogen-fixing activity to later stages of ontogenesis (Pavlyshche et al, 2017).…”
Section: Photosynthetic Apparatus Capacity and Plant Productivitymentioning
confidence: 60%